DISEÑO DE UNA POLÍTICA PÚBLICA PARA LA GENERACIÓN DE PROYECTOS PRODUCTIVOS EN LOS JÓVENES DE 18 A 29 AÑOS DE LA CIUDAD DE LOJA EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DE LOJA PERIODO 2012-2013 - Reyes Rivera, Estefanía Judith (2016)
This research refers to the topic called: Design of public policy for the generation of productive projects in the 18- to 29 years of the city of Loja in the Autonomous Decentralized Municipal Government of Loja period 2012-2013 and is analyzing the role of the State through its national and sectoral public policies; the scope, implementation, strategies, programs and projects aimed at promoting dynamic development, and likewise the process of articulation of the different public actors to help improve the living conditions of the population by supporting entrepreneurship. The purpose of this study is not only a diagnosis of entrepreneurship of young people in the city of Loja, but also help to know that many young professionals can not find the facilities for the establishment of business initiatives, for it was established the most important characteristics of entrepreneurship considering all social and economic factors, political, theoretical. To fulfill research study methodology was established through a stratified sample, applying a survey of young people between 18 to 29 years of the city of Loja, one interview was also carried the Director of the Department of Management microenterprise Municipal Decentralized Autonomous Government of Loja, and director of microenterprise Management Provincial Autonomous Government of Loja, which determined the efforts being made to strengthen and promote entrepreneurship in the city. 5 The main results identified the existence of a lack of support for youth entrepreneurship by public actors, was further reflected the lack of a coordinated public policy to support this goal, so a policy to support entrepreneurship was raised, the proposal it is aimed at reviving the enterprises in the city of Loja As for the argument the existence of low levels of entrepreneurship in young people due to lack of seed capital, public support and youth defection to these problems affecting the productivity of Loja was analyzed. In the final part of the research findings and recommendations necessary to foster an entrepreneurial culture in young people, considered the most vulnerable sector of the city arise.